The longest survival after mitral valve replacement with a tilting-disc Lillehei-Kaster prosthesis? - Jander, Sławomir; Bartczak, Karol; Bitner, Mirosław; Zielińska, Marzenna (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
In 1960, Starr implanted the first mitral valve prosthesis, starting the era of mitral valve replacement (MVR). Since that time, millions of valve devices have been implanted and many patients have been followed-up and reported. However, it is difficult to find reports regarding cases of more than 25-year survival after MVR. Therefore, we present a unique case of the patient who underwent MVR with the Lillehei-Kaster prosthesis on 14 March 1979. During the 32-year follow-up the patient had some events (infective, thromboembolic and hemorrhagic) but they were effectively treated. Through the observation period he remained in functional class II of the New York Heart Association on optimized medical therapy regimen. The most recent echocardiography showed a relatively good functioning mitral prosthesis with a small effective orifice area of 1.0 cm 2 and transvalvular gradient of 13/6 mm Hg. The 32-year survival after MVR is an excellent and rarely seen result.